Role of Rituximab in miraculous cessation of ventricular tachycardia in Granulomatosis with polyangiitis: a case report - Sultan, Nadia; Mushtaq, Fahad; Noor, Natasha; Ullah, Zafar; Saleem, Asad Ali (Journal of the Pakistan Medical Association, 2022)
Granulomatosis with polyangiitis (GPA) is a rare systemic disorder of unknown aetiology. The histological findings comprise necrotising granulomatous inflammation of small arteries, arterioles, and the capillaries mainly of upper and lower respiratory tract and the kidneys. However, the disease rarely involves the cardiovascular system but may manifest as pericarditis, myocarditis, coronary arteritis, valvular lesions, and severe conduction disorders. We present an interesting, unusual, and complex case of a middle-aged man who initially presented with symptoms suggestive of Wagener’s granulomatosis but two years later developed malignant ventricular arrhythmias. A diagnosis of exclusive involvement of the cardiac conduction system, without overt myocarditis, was made only after ruling it out by cardiac MRI, cardiac enzymes, echo, and normal serological markers. Evidence was paired with the cessation of monomorphic ventricular tachycardia due to induction therapy with Rituximab. In this case report, we highlight one of the rarest manifestations of GPA, i.e. Ventricular tachycardia Continuous...